A new cicada species of the genus Psithyristria Stål, 1870 (Hemiptera: Cicadidae: Cicadinae: Psithyristriini) from Luzon, Philippines, with a key to the 15 species - Lee, Young June; Lit, Ireneo L. Jr. (Zootaxa, 2015)
A new species of the genus Psithyristria Stål, 1870, Psithyristria ridibunda sp. nov., is described from Quezon, Luzon, Philippines. The new species is very similar to Psithyristria incredibilis Lee & Hill, 2010, but the cubital cell is distinctly larger than the radial cell and the medial branch of the uncal lobe is much shorter than the lateral branch and has two tiny apical spines. Psithyristria isarogensis Boulard & Yap, 2013 is synonymized with Psithyristria paracrassis Lee, 2010. A revised key to the 15 species of Psithyristria is provided.